2018
DOI: 10.1002/clc.22966
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography scar quantification correlates with scar size of hypertrophic cardiomyopathy seen by multidetector computed tomography

Abstract: The Selvester QRS score provides reliable quantification of myocardial fibrosis and was well correlated with MDCT in patients with HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…Comparing our results with that of the other methods listed in Table 2, it must be taken into account that the underlying cohorts differ in size, structure and time of study. Considering the larger training sets used by Goovaerts et al (2019) and by Dima et al (2013) and the limited number of cases used by Chaudhry et al (2017) and Bignoto et al (2018), our results are similar. For a more substantiated comparison, the methods would have to be applied to the identical data, see Bengio and Grandvalet (2004).…”
Section: Model Performancesupporting
confidence: 62%
“…Comparing our results with that of the other methods listed in Table 2, it must be taken into account that the underlying cohorts differ in size, structure and time of study. Considering the larger training sets used by Goovaerts et al (2019) and by Dima et al (2013) and the limited number of cases used by Chaudhry et al (2017) and Bignoto et al (2018), our results are similar. For a more substantiated comparison, the methods would have to be applied to the identical data, see Bengio and Grandvalet (2004).…”
Section: Model Performancesupporting
confidence: 62%
“…This study provides one of the first analyses using a 3 Tesla CMR and a simplified quantification method for QWA compared to the previously more complicated method for QWA quantification. 10 , 11 , 12 , 13 Our enrolled subjects had stable infarct size due to timing of CMR assessment in contrast to previous studies on acute myocardial infarctions. 14 Our results support the same direction found in prior studies revealing the correlation between global QWA and total scar volume.…”
Section: Discussionmentioning
confidence: 89%
“…The amount of myocardial fibrosis is not a component of traditional surgical risk scores, and in the literature some studies have reported a correlation between the amount of fibrosis and mortality, both in other heart diseases 17,18,30 and also in AS 31 . Other publications have shown that the Selvester QRS score was well correlated with the estimation of fibrosis and cardiac imaging studies 32‐36 . Other publications have shown that use of the Selvester QRS score should be used with caution in patients with low LV ejection fraction and LBBB 37 .…”
Section: Discussionmentioning
confidence: 99%
“…31 Other publications have shown that the Selvester QRS score was well correlated with the estimation of fibrosis and cardiac imaging studies. [32][33][34][35][36] Other publications have shown that use of the Selvester QRS score should be used with caution in patients with low LV ejection fraction and LBBB. 37 In patients with low pretest probability of myocardial scar, Selvester QRS score requires greater clinical evidence.…”
Section: Discussionmentioning
confidence: 99%